The Traitor, the Infidel, and the Wretch:: an analysis of three stereotypes of translation - Hottinger-Craig, Sylvia (2021)
The Traitor, the infidel, and the Wretch: an analysis of three stereotypes of translation This paper is a review of theoretical issues in translation studies via the three most common stereotypes on the subject. A translator  was seen as the traitor, Traductore tradittore, who doesn’t convey all that is said the text, due to the inability transfer all the linguistic knowledge of one culture to another, and that is if the traitor does not pertain to the Other culture and is keeping information to his self. While the Belle infidele will not be beautiful if the translation is too literal and the opposite situation. Since the language of the paper and its sources are Spanish we have included Ortega y Gasset’s the Misery and Splendor of translation as a third metaphor for translation issues. We also include a summary of Mona baker’s and Peter Newmark’s translation techniques. Our goal was to consider translation studies from an empirical and professional perspective.